SPECIFICATION OF APPEARANCES OF COMPREHENSIVE FORMS IN UZBEK LANGUAGE MORPHEMES - URALOVA GAVHAR TUGALOVNA (Scholar Express Journals, 2022)
The scientific and theoretical views of many linguists are expressed in this article, which includes some types and manifestations of the extended forms in the morphology of the Uzbek language. The formation of expanded forms, their role in the development of the language is revealed. In addition to this, the article reflects the opinions of linguists. The ideas are proved with the help of various examples
Keywords: Morpheme; morphs; syntagms; compound affixes